Penerapan Total Quality Management Dalam Peningkatan Mutu Satuan Pendidikan - Zulfa, Eva; Halimatuzzahrah, Halimatuzzahrah (STAI Darul Kamal NW Kembang Kerang, 2025)
This research aims to analyze the implementation of quality-based management in improving the quality of education at Madrasah Ibtidaiyah Nurul Hikmah Lantan. The main focus of this research is to identify the problems faced, examine the potential for implementing quality-based management, and provide strategic recommendations for improving quality-based education management. The method used in this research is a qualitative approach with data collection techniques through in-depth interviews, observation and documentation studies. The results of the research show that the implementation of quality-based management in this madrasa is still limited, especially in aspects of decision making that are not yet data-based, weak coordination between madrasa heads and educators, and evaluations that are more immoral in nature. formality without concrete follow-up. Obstacles faced include limited trained human resources, inadequate facilities, and low involvement of stakeholders such as parents and the community in supporting education policies. However, this research also identifies great potential in implementing quality-based management, including by increasing human resource capacity through training, using technology for data management and evaluation, and strengthening coordination and communication between stakeholders.